Improvement of microstructures and dielectric properties of coprecipitation iron (Fe)-doped barium titanate - Muazaroh Nur Azizah; Dianisa Khoirum Sandi; Khairuddin Khairuddin; Fahru Nurosyid; Trya Andini; Yofentina Iriani (Journal of Physics: Theories and Applications, 2026)
Barium titanate (BaTiO3 or BTO) is a famous lead-free ferroelectric material often studied due to its fascinating features for technological applications. However, its performance requires continuous enhancement, one approach being doping with iron (Fe). This study aimed to demonstrate the improvement in the microstructures and dielectric properties of barium titanate induced by iron doping. The barium titanate and iron-doped barium titanate with the formula of BaTi1-xFexO3 (x = 0, 0.01, 0.03, and 0.05) were synthesized using the coprecipitation technique. X-ray diffraction (XRD) analysis confirmed the formation of a pure tetragonal phase in all samples, while Fourier-transform infrared (FTIR) spectroscopy revealed characteristic BTO absorption bands at around 500 cm−1. Compared with pure BTO, Fe-doped samples exhibited increased lattice constants, crystallite sizes, densities, and dielectric constants. Further, the dielectric constants of the samples were also higher than those of undoped barium titanate. These results indicate that Fe doping enhances the microstructures of BTO, leading to improved dielectric performance.